Interaction of irritability and anxiety on emotional responding and emotion regulation: a functional MRI study. Issue 16 (25th December 2021) - Crum, Kathleen I.; Hwang, Soonjo; Blair, Karina S.; Aloi, Joseph M.; Meffert, Harma; White, Stuart F.; Tyler, Patrick M.; Leibenluft, Ellen; Pope, Kayla; Blair, R. J. R.
Abstract: Background: Irritability and anxiety frequently co-occur in pediatric populations. Studies separately looking at the neural correlates of these symptoms have identified engagement of similar neural systems – particularly those implicated in emotional processing. Both irritability and anxiety can be considered negative valence emotional states that might relate to emotion dysregulation . However, previous work has not examined the neural responding during the performance of an emotion regulation task as a function of interaction between irritability and anxiety simultaneously. Methods: This fMRI study involved 155 participants (90 with significant psychopathologies and 92 male) who performed the Affective Stroop Task, designed to engage emotion regulation as a function of task demands. The Affective Reactivity Index (ARI) was used to index irritability and the Screen for Child Anxiety Related Emotional Disorders (SCARED) was used to index anxiety. Results: Levels of irritability, but not anxiety, was positively correlated with responses to visual images within the right rostro-medial prefrontal cortex and left anterior cingulate cortex during view trials. The second region of ventral anterior cingulate cortex showed a condition-by-emotion-by-ARI score-by-SCARED score interaction. Specifically, anxiety level was significantly correlated with a decreased differential BOLD response to negative relative to neutral view trials but only in the presence of relatively high irritability . Conclusions: Atypical maintenance of emotional stimuli within the rostro-medial prefrontal cortex may exacerbate the difficulties faced by adolescents with irritability. Moreover, increased anxiety combined with significant irritability may disrupt an automatic emotional conflict-based form of emotion regulation that is particularly associated with the ventral anterior cingulate cortex.